2019
DOI: 10.3390/ijerph16244946
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Expanded Focus for Occupational Safety and Health: A Commentary

Abstract: Powerful and ongoing changes in how people work, the workforce, and the workplace require a more holistic view of each of these. We argue that an expanded focus for occupational safety and health (OSH) is necessary to prepare for and respond rapidly to future changes in the world of work that will certainly challenge traditional OSH systems. The WHO Model for Action, various European efforts at well-being, and the Total Worker Health concept provide a foundation for addressing changes in the world of work. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 71 publications
(121 reference statements)
0
102
0
4
Order By: Relevance
“…A smart manufacturing environment is not only designed to make production processes more automated and efficient, but also to bring forth the scope and convenience of flexible or remote work in a decentralized manufacturing ecosystem driven by CPPS, while ensuring safety and risk assessment in production facilities. [87,88] A detailed review on the focus for occupational health and safety within the context of evolving manufacturing practices is provided by Schulte et al [89] Palazon et al [90] suggested that wireless sensor networks when effectively and appropriately integrated with the physical systems would substantiate the autonomous and intelligent platforms in manufacturing settings and preventing accidents. This was further supported by Gisbert et al [91] as the authors maintained that digital technologies such as IoT and AI have the capability to detect or predict operational hazards and dangers in the workplace and guarantee the reliability of such integrated systems and separate remote centers to monitor their function, and performance has to be implemented.…”
Section: Safety Security and Flexible Operationsmentioning
confidence: 99%
“…A smart manufacturing environment is not only designed to make production processes more automated and efficient, but also to bring forth the scope and convenience of flexible or remote work in a decentralized manufacturing ecosystem driven by CPPS, while ensuring safety and risk assessment in production facilities. [87,88] A detailed review on the focus for occupational health and safety within the context of evolving manufacturing practices is provided by Schulte et al [89] Palazon et al [90] suggested that wireless sensor networks when effectively and appropriately integrated with the physical systems would substantiate the autonomous and intelligent platforms in manufacturing settings and preventing accidents. This was further supported by Gisbert et al [91] as the authors maintained that digital technologies such as IoT and AI have the capability to detect or predict operational hazards and dangers in the workplace and guarantee the reliability of such integrated systems and separate remote centers to monitor their function, and performance has to be implemented.…”
Section: Safety Security and Flexible Operationsmentioning
confidence: 99%
“…This paradigm shift challenges traditional OSH systems by focusing on worker well-being as an outcome, goes beyond the prevention of workplace injury and illness or health promotion, and expands the types of hazards typically considered in the traditional OSH paradigm. The World Health Organization (WHO) Model for Action, various European efforts at well-being, and the NIOSH TWH Program provide important foundations for addressing changes in the world of work [ 9 ]. Beyond this, though, we need a more expansive paradigm to include greater recognition of both individual worker and workforce well-being as important OSH outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond this, though, we need a more expansive paradigm to include greater recognition of both individual worker and workforce well-being as important OSH outcomes. Embracing this paradigm shift mandates a more expansive, systems thinking approach to better integrate traditional OSH with personal and socioeconomic risk factors, both horizontally (broadening the range of factors to examine their impact on health) and vertically (from a short-term, single job perspective to a work life continuum perspective encompassed by the overarching concept of well-being) [ 9 ]. This will require greater interprofessionalism, collaborative organizational leadership, proactive company policies, accountability, training, and engagement of management and employees, as well as following benchmarks over time and identifying opportunities for early corrective or enhancing interventions [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies no clear distinction between environmental and occupational health, as many of the factors that create the structural vulnerabilities in these worker populations are societal problems that go beyond the realm of occupational health and merge into larger public health questions. 70,71 In this perspective, interdisciplinary research should be a priority, just as a decompartmentalization of scientific disciplines would be relevant and appropriate in this emerging sector. Health inequities are then viewed from a macro socioeconomical perspective that identifies many of the situations of vulnerability, experienced by individuals who belong to disadvantaged groups in society, and that commonly affect persons working also in disadvantageous conditions.…”
Section: Research Needs and Recommendationsmentioning
confidence: 99%